An Analysis on the Students’ Writing Skill in Online Class - Yusrita Amelia (Journal of English Language and Education, 2020)
This research aims to describe how students' writing skills in expressing opinion text by using the Google Classroom application and to find out problems in the online class by using Google Classroom at eleventh grade of SMAN 2 Kuok academic year 2019/2020. The method used is descriptive research. The subjects of this research consists of 34 students of class XI IIS and class XI MIPA. The researchers used two instruments, those were test and questionnaire. Based on, the analysis of the research showed that the average of the students' achievement in writing was 51. The results of the questionnaire 8 or 24% of students were able to learn to expression opinion texts well using Google Classroom. Meanwhile, 13 or 38% did not understand writing opinion texts. In addition, the test results shows that students' writing skills in expressing opinion text by using Google Classroom were are at a weak level. From the questionnaire data, it shows that students do not understand and find it difficult to write text to expression opinion by using Google Classroom and have difficulty getting a good network because of the data package they use. Students are often late in sending assignments to the teacher because of the network problems used. It can be concluded that students' writing skills in expressing opinion texts using Google Classroom are still low.